Language Argumentation and Thought Mechanisms: A Cognitive Linguistic Approach (Linguist, 2021)
This study addresses some of the foundations and mental dimensions of the issue of Al-Hijaj (Argumentation), in terms of the mechanisms of brain work, and the conceptual overlapping between the issues of Argumentation, proof and controversy (Dialectical Conversation). Research Items focus on philosophical rhetorical issues, and micro- linguistics, applying to some examples, especially the Holy Qur’an. The research adopts examples from the Holy Qur’an because it represents a methodological basis and main Corpus for many of the normative structures related to Argumentation, which can be compared to later. We have also presented some general philosophical approaches related to all these intersections, because of their intellectual importance, which represent, as well, a starting point towards more in-depth and useful discussions in later studies.
Keywords: Argumentation; Thought; Mind; Holy Qur’an; Linguistics; Philosophy